Study on acoustic emission evolution features of gas-bearing coal under different gas pressures - Yejiao Liu; Fu Gao; Wenjie Yan; Zeyu Duan; Guangbo Chen; Fengyi Jiang; Zhichao Tian; Jinliang Li (Scientific Reports)
Abstract To explore gas pressure of coal samples under uniaxial compression condition the influence of the acoustic emission features, based on the uniaxial compression acoustic emission monitoring test, the acoustic emission parameters of coal samples under different gas pressure gradients are monitored and analyzed. The gas version RFPA2D simulation software was used to simulate the spatial and temporal evolution of acoustic emission of coal samples under different gas pressure conditions. The results show that the acoustic emission feature parameters of gas-bearing coal samples show a significant linear decreasing trend with the increase of gas pressure. It can be seen that the increasing gas pressure inside the coal sample will expand the damage range of the simulated coal sample, and the amount of loading steps required for the occurrence of peak count and peak energy of acoustic emission when the coal sample destruction reaches the critical state are significantly reduced, which can accelerate the damage-fracture transformation process of the loaded coal rock. This study can effectively expose the the mechanism of coal and gas outburst disaster-inducing, which provides an important theoretical basis for the prevention and control of coal and gas outburst.